The Intervention Effect of Traditional Chinese Medicine on the Intestinal Flora and Its Metabolites in Glycolipid Metabolic Disorders. (4th June 2019) - Di, Sha; Wang, Yitian; Han, Lin; Bao, Qi; Gao, Zezheng; Wang, Qing; Yang, Yingying; Zhao, Linhua; Tong, Xiaolin
Abstract : Metabolic syndrome (MS), which includes metabolic disorders such as protein disorder, glucose disorder, lipid disorder, and carbohydrate disorder, has been growing rapidly around the world. Glycolipid disorders are a main type of metabolic syndrome and are characterized by abdominal obesity and abnormal metabolic disorders of lipid, glucose, and carbohydrate utilization, which can cause cardiovascular and cerebrovascular diseases. Glycolipid disorders are closely related to intestinal flora and its metabolites. However, studies about the biological mechanisms of the intestinal flora and its metabolites with glycolipid disorders have not been clear. When glycolipid disorders are treated with drugs, a challenging problem is side effects. Traditional Chinese medicine (TCM) and dietary supplements have fewer side effects to treat it. Numerous basic and clinical studies have confirmed that TCM decoctions, Chinese medicine monomers, or compounds can treat glycolipid disorders and reduce the incidence of cardiovascular disease. In this study, we reviewed the relationship between the intestinal flora and its metabolites in glycolipid metabolic disorders and the effect of TCM in treating glycolipid metabolic disorders through the intestinal flora and its metabolites. This review provides new perspectives and strategies for future glycolipid disorders research and treatment.